Dietary intakes, nutritional habits, and nutritional supplement use of collegiate athletes: a sample from a university in Turkey - Mengi Çelik, Özge; Dağdeviren, Hamdi Nezih (Progress in Nutrition, 2022)
Objective: There is no published data about dietary intakes, nutritional habits, and supplement use of Turkish collegiate athletes who are actively competing in any sports branch. This study aimed to assess supplement use, nutritional habits, and dietary intakes in collegiate athletes.Participants and Methods: One hundred twenty-seven athletes participated in this study.Results: The energy intake was 3084.3±1564.0 kcal in women and 3981.9±1531.7 kcal in men. Energy and all nutrient intakes were above the recommended level. It was found that 49.6% of the athletes used nutritional supplements (≥2 days/week over the past year). The most used supplements were sports drinks (33.1%), multivitamin/mineral supplements (26.0%), and protein powder (21.3%). Athletes learned the information about supplements mostly from coaches (31.5%), internet (28.3%), and friends (21.3%). It was found that 51.2% of the athletes skipped meals.Conclusion: Nutrition education is needed to improve nutritional habits and dietary intakes of collegiate athletes.